FATE OF DOMINANT FOLLICLE IN SUMMl;R ANESTRUS BUFFALOES - GHUMAN, S P S; SINGH, JAGIR; HONPARKHE, M; DADARWAL, D; DHALIWAL, G S; SINGH, S T (The Indian Journal of Animal Reproduction, 2023)
During peak summer for a period of 24 days, anestrus (n=6) and cycling (n=5) buffaloes were subjected totransrectal ovarian ultrasonog raphy and jugular vein blood sampling on alternate days. During this period, anestrusbuffaloes exhibited successive development of follicles which reached dominant phase (19 follicles, 12.6±0.3 mmdiameter) but remained non-ovulatory. The diameter of ovulatory follicles (6 follicles) in cycling buffaloes was·· 13.1 ±0. 8 mm. Plasma progesterone in an estrus and cycling buffaloes was 0.1 ±0.0 and 0. 71 ±0.03 ng/ml (p
Keywords: Anestrus; Buffalo; Follicle; Progesterone; Summer